2016
DOI: 10.1017/s1743921317004045
|View full text |Cite
|
Sign up to set email alerts
|

Tidal effects on stellar activity

Abstract: Abstract. The architecture of many exoplanetary systems is different from the solar system, with exoplanets being in close orbits around their host stars and having orbital periods of only a few days. We can expect interactions between the star and the exoplanet for such systems that are similar to the tidal interactions observed in close stellar binary systems. For the exoplanet, tidal interaction can lead to circularization of its orbit and the synchronization of its rotational and orbital period. For the ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Alternative activity indicators have been used to search for evidence that tidal interactions stoke stellar activity (see reviews by Wright and Miller 2015;Poppenhaeger 2017). For example, Poppenhaeger and Wolk (2014) and Miller et al (2015) found enhanced stellar coronal Xray emission from host stars that are expected to have strong tidal interactions with their hot Jupiters.…”
Section: The Possible Role Of Stellar Obliquitymentioning
confidence: 99%
“…Alternative activity indicators have been used to search for evidence that tidal interactions stoke stellar activity (see reviews by Wright and Miller 2015;Poppenhaeger 2017). For example, Poppenhaeger and Wolk (2014) and Miller et al (2015) found enhanced stellar coronal Xray emission from host stars that are expected to have strong tidal interactions with their hot Jupiters.…”
Section: The Possible Role Of Stellar Obliquitymentioning
confidence: 99%